Impact of T-shaped skill and top management support on innovation speed; the moderating role of technology uncertainty - Hamdi, Shabnam; Silong, Abu Daud; Omar, Zoharah; Mohd Rasdi, Roziah (Cogent OA, 2016)
This study examines the moderating role of technology uncertainty on the relationship between team contextual factors of top management support and T-shaped skills with innovation speed. For the purpose of this study, the data were collected from 227 new products from 147 biotechnology firms in Malaysia. The overall results confirmed the moderating effect of technology uncertainty on the relationship between T-shaped skills, as well as top management support with innovation speed. The results further confirmed that under the high technology uncertainty, this effect is higher in comparison to the low and medium uncertainty. This indicates that the effect of top management support and T-shaped skills on innovation speed improves when technology uncertainty increases. On the practical side, the report equips biotech firms with valuable insights to develop effective strategies.